Ruth : Justice Ginsburg in her own words [videorecording (DVD)] - Ginsburg, Ruth Bader, 1933-2020; Golán, M. A., 1989-; Mock, Freida Lee; Haydn, Lili; Lenzer, Don; Rainey, Rob; Roland, Erich; Shenk, Jon (Kino Lorber, 2021)
Ruth: Justice Ginsburg in her own Words tells the improbable story of how Ruth Bader Ginsburg, who couldn't get a job despite graduating first in her law school class in a tie and making Law Review at Harvard and Columbia Law Schools, became an Associate Justice of the Supreme Court. It also reveals both the public and private sides of a resilient, resourceful woman who has survived the hostility of the profoundly male universe of government and law to become a revered Justice and icon for gender equality and women's rights.